DESIGN OF SWIMMING POOL EMPLOYEES HONORARIUM OF LEBAK BULUS JAKARTA - Hesti Sulistyowati; Eko Hadiyanto,SSI, MM (Jurnal Sistem Informasi, 2000)
We can conclude that in the salary payment system of employees here, the processingof data (such as data entry basensi employees) must be done carefully, so that thefunction of this administration accountable.The use of employee salary payment system is expected to not too difficult in theiruse, so that what the author expected can be achieved.